2019
DOI: 10.1111/jnc.14715
|View full text |Cite
|
Sign up to set email alerts
|

Activation of peroxisome proliferator‐activated receptor delta suppresses BACE1 expression by up‐regulating SOCS1 in a JAK2/STAT1‐dependent manner

Abstract: Neuronal expression of beta-secretase 1 (BACE1) has been implicated in the progression of Alzheimer's disease. However, the mechanisms that regulate BACE1 expression are unclear. Here, we show that peroxisome proliferator-activated receptor delta (PPARd) decreases BACE1 expression by upregulating suppressor of cytokine signaling 1 (SOCS1) in SH-SY5Y neuroblastoma cells. The activation of PPARd by GW501516, a specific PPARd agonist, inhibited expression of BACE1. This effect was abrogated by shRNA-mediated knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…A peptides directly and indirectly activate TLR4, the pattern recognition receptor for LPS (29,30). STAT1 tis sue concentration is increased in diseased regions of AD brain (31) and can regulate expression of  secretase 1, one of the endoproteases that sequentially catalyzes the hydrolysis of amyloid precursor pro tein to generate A peptides (32). STAT5 activation regulates micro glial activation and is required for monocytemediated synaptic degradation (33).…”
Section: Discussionmentioning
confidence: 99%
“…A peptides directly and indirectly activate TLR4, the pattern recognition receptor for LPS (29,30). STAT1 tis sue concentration is increased in diseased regions of AD brain (31) and can regulate expression of  secretase 1, one of the endoproteases that sequentially catalyzes the hydrolysis of amyloid precursor pro tein to generate A peptides (32). STAT5 activation regulates micro glial activation and is required for monocytemediated synaptic degradation (33).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that PPARδ activation may exert a neuroprotective effect in AD models by inhibiting the inflammation and the amelioration of Aβ 1-42 -induced hippocampal neurotoxicity ( 58 , 59 ). Additionally, PPARδ has been demonstrated to suppress the generation of neurotoxic Aβ by attenuating BACE1 expression via the cytokine signaling 1-mediated inhibition of signal transducer and activator of transcription 1 signaling ( 60 ). In the present study, only the effects of ginsenoside Rg1 on PPARγ were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also evidence the enhanced transcription of two genes under the NFκB transcriptional control, that encode members of the STAT protein family of transcription factors ( STAT1 and STAT5 ) and are involved in many aspects of cellular immunity, proliferation, apoptosis, and differentiation. 73 Moreover, STAT1 can regulate the expression of β secretase 1 for the generation of Aβ peptides, 74 while STAT5 seems to regulate microglial activation. 75 …”
Section: Discussionmentioning
confidence: 99%
“…Our findings also evidence the enhanced transcription of two genes under the NFκB transcriptional control, that encode members of the STAT protein family of transcription factors (STAT1 and STAT5) and are involved in many aspects of cellular immunity, proliferation, apoptosis, and differentiation. 73 Moreover, STAT1 can regulate the expression of β secretase 1 for the generation of Aβ peptides, 74 while STAT5 seems to regulate microglial activation. 75 Apoptosis-modulating NFκB targets were also found overexpressed in the blood of the investigated AD patients, including the genes encoding the pro/anti-apoptotic Bcl-2like protein 1 (BCL2L1) and AKT1, as well as the apoptosis inducer Fas ligand (FASLG).…”
Section: Dovepressmentioning
confidence: 99%